You're not tweeting any more!. Issue 7 (2014) - Unknown
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to review the latest management developments across the globe and pinpoint practical implications from cutting‐edge research and case studies. Design/methodology/approach – This briefing is prepared by an independent writer who adds his/her own impartial comments and places the articles in context. Findings – In July, the football and pop worlds were rocked by the shocking news that, almost unbelievably, diva Rihanna had been overtaken as the fifth most popular Facebook page by Portuguese forward Cristiano Ronaldo, who was adding 175, 000 page likes a day. Like, OMG. Practical implications – This paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Original/value – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy‐to‐digest format.